Labour Migration and Remittances: Strategy for Survival or Development? - Kurmanov, Nurlan; Baktymbet, Saule; Baktymbet, Assem; Rakhimbekova, Assel; Sagindykova, Gulnara; Satbayeva, Aizhan; Baidakov, Asylbek (International Journal of Economics and Financial Issues, 2017)
The article is devoted to an actual problem of labor migration, the study of remittances and their role in the lives of migrant households. Remittances are used in migrant households in Central Asia primarily for the purchase of consumer goods. Since labor migration flows in the region tend to increase, and the volume of remittances increase, it becomes much more urgent to use the remittances not only for consumption, but also for development. To develop the programs on the use of remittances for the development of outcomes in the countries and for the achievement there is a need to study the problem comprehensively: the volumes and methods of transfers, their role in migrant households and national economies. Keywords: Labour migration, Migrant remittances, Central Asia, Kazakhstan JEL Classifications: F22, J61